The effects of anodal-tDCS on corticospinal excitability enhancement and its after-effects: conventional vs. unihemispheric concurrent dual-site stimulation - Vaseghi, Bita; Zoghi, Maryam; Jaberzadeh, Shapour (Frontiers in Human Neuroscience, 2015)
Previous researchers have approved the ability of anodal transcranial direct current stimulation (a-tDCS) of the primary motor cortex (M1) to enhance corticospinal excitability (CSE). The primary aim of the current study was to investigate the effect of concurrent stimulation of M1 and a functionally connected cortical site of M1 on CSE modulation. This new technique is called unihemispheric concurrent dual-site a-tDCS (a-tDCSUHCDS). The secondary aim was to investigate the mechanisms underlying the efficacy of this new approach in healthy individuals. In a randomized crossover study, 12 healthy right-handed volunteers received a-tDCS under five conditions: a-tDCS of M1, a-tDCSUHCDS of M1-dorsolateral prefrontal cortex (DLPFC), a-tDCSUHCDS of M1-primary sensory cortex (S1), a-tDCSUHCDS of M1-primary visual cortex (V1), and sham a-tDCSUHCDS. Peak-to-peak amplitude of transcranial magnetic stimulation (TMS) induced MEPs, short-interval intracortical inhibition (SICI) and intracortical facilitation (ICF) were assessed before and four times after each condition. A-tDCSUHCDS conditions induced larger MEPs than conventional a-tDCS. The level of M1 CSE was significantly higher following a-tDCSUHCDS of M1-DLPFC than other a-tDCSUHCDS conditions (p < 0.001), and lasted for over 24 h. The paired-pulse TMS results after a-tDCS of M1-DLPFC showed significant facilitatory increase and inhibitory change. A-tDCSUHCDS of M1-DLPFC increases M1 CSE twofold that of conventional a-tDCS. A-tDCSUHCDS of M1-DLPFC enhances the activity of glutamergic mechanisms for at least 24 h. Such long-lasting M1 CSE enhancement induced by a-tDCSUHCDS of M1-DLPFC could be a valuable finding in clinical scenarios such as learning, motor performance, or pain management. The present study has been registered on the Australian New Zealand Clinical Trial at http://www.anzctr.org.au/ with registry number of ACTRN12614000817640.